How the North American Consensus Protocol Affects the Performance of Glucose Breath Testing for Bacterial Overgrowth Versus a Traditional Method. (28th April 2021) - Baker, Jason R.; Chey, William D.; Watts, Lydia; Armstrong, Moira; Collins, Kristen; Lee, Allen A.; Dupati, Ajith; Menees, Stacy; Saad, Richard J.; Harer, Kimberly; Hasler, William L.
Abstract : INTRODUCTION: The North American Consensus guidelines for glucose breath testing (GBT) for small intestinal bacterial overgrowth (SIBO) incorporated changes in glucose dosing and diagnostic cutoffs. We compared GBT positivity based on hydrogen and methane excretion and quantified symptoms during performance of the North American vs older modified Rome Consensus protocols. Methods: GBT was performed using the North American protocol (75 g glucose, cutoffs > 20 parts per million [ppm] hydrogen increase after glucose and > 10 ppm methane anytime) in 3, 102 patients vs modified Rome protocol (50 g glucose, > 12 ppm hydrogen and methane increases after glucose) in 3, 193 patients with suspected SIBO. Results: Positive GBT were more common with the North American vs modified Rome protocol (39.5% vs 29.7%, P < 0.001). Overall percentages with GBT positivity using methane criteria were greater and hydrogen criteria lower with the North American protocol ( P < 0.001). Peak methane levels were higher for the North American protocol ( P < 0.001). Times to peak hydrogen and methane production were not different between protocols. With the North American protocol, gastrointestinal and extraintestinal symptoms were more prevalent after glucose with both positive and negative GBT ( P < 0.04) and greater numbers of symptoms ( P < 0.001) were reported. DISCUSSION: GBT performed using the North American Consensus protocol was more often positive for SIBO vs the modified Rome protocol because of more prevalent positive methane excretion. Symptoms during testing were greater with the North American protocol. Implications of these observations on determining breath test positivity and antibiotic decisions for SIBO await future prospective testing.